Kings of the sea Charles II, James II and the Royal Navy - Davies, J. D. 1957- (Seaforth Publishing, 2017)
"It has always been widely accepted that the Stuart kings, Charles II and James II, had an interest in the navy and more generally in the sea. Their enthusiastic delight in sailing, for instance, is often cited as marking the establishment of yachting in England. The major naval developments in their reigns on the other hand developments that effectively turned the Royal Navy into a permanent, professional fighting force for the first time have traditionally been attributed to Samuel Pepys. This new book, based on a wide range of new and previously neglected evidence, presents a provocative new theory: that the creation of the proper Royal Navy was in fact due principally to the Stuart brothers, particularly Charles II, who is presented here, not as the lazy monarch neglectful of the detail of government, but as a king with an acute and detailed interest in naval affairs. The author also demonstrates that Charles Stuart predecessors were far more directly involved in naval matters than has usually been allowed, and proves that Charles and James command of ship design and other technical matters went well beyond the bounds of dilettante enthusiasm. It is shown how Charles in particular, intervened in ship design discussions at a highly technical level; how the brothers were principally responsible for the major reforms that established a permanent naval profession; and how they personally sponsored important expeditions and projects such as Greenvile Collins survey of British waters. The book also reassesses James II s record as a fighting admiral. It is a fascinating journey into the world of the Stuart navy and shows how the Kings of the Sea were absolutely central to the development of its ships, their deployment and the officer corps which commanded them; it offers a major reassessment of that dynasty s involvement in naval warfare"-- Publisher description
Keywords: Karl -- II. -- England, König -- 1630-1685; Jakob -- II. -- England, König -- 1633-1701; Marine; England; Great Britain / Royal Navy / History; Great Britain / Royal Navy; Great Britain / History, Naval / Stuarts, 1603-1714; Great Britain; 1603-1714; History; Naval history; Bibliografie